2019
DOI: 10.1101/823849
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Extensive functional repertoire underpins complex behaviours: insights from Parkinson’s disease

Abstract: Rapid reconfigurations of brain activity support efficient neuronal communication and flexible behaviour. Suboptimal brain dynamics impair this adaptability, possibly leading to functional deficiencies. We hypothesize that impaired flexibility in brain activity can lead to motor and cognitive symptoms of Parkinson's disease (PD). To test this hypothesis, we studied the 'functional repertoire' the number of distinct configurations of neural activityusing source-reconstructed magnetoencephalography in PD patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 105 publications
(140 reference statements)
0
8
0
Order By: Relevance
“…S1), the identifiability of the patients drops drastically as compared to controls. Previous evidence showed that the large-scale activity in the healthy brain is fine-tuned to achieve both efficient communication and functional reconfiguration, which underpins complex, adaptable behavioural responses (24,25). Therefore, this finding might be framed within the dysregulation of large-scale activity due to the pathological processes.…”
Section: Discussionmentioning
confidence: 97%
“…S1), the identifiability of the patients drops drastically as compared to controls. Previous evidence showed that the large-scale activity in the healthy brain is fine-tuned to achieve both efficient communication and functional reconfiguration, which underpins complex, adaptable behavioural responses (24,25). Therefore, this finding might be framed within the dysregulation of large-scale activity due to the pathological processes.…”
Section: Discussionmentioning
confidence: 97%
“…2.5 and 3.5) were tested. An avalanche was defined as starting when any region is above threshold, and finishing when no region is active, as in 15 . Avalanches shorter than 10 time bins were excluded in the reported results.…”
Section: Methodsmentioning
confidence: 99%
“…MEG pre-processing MEG pre-processing and source reconstruction were performed as in 15 . In short, the data were acquired using a MEG system equipped by 154 SQUID magnetometers (Superconducting However, when these regions were included, the results were replicated.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, pathological conditions that disrupt this optimally tuned configuration are deleterious, either as excessive disconnections as in Alzheimer disease (Heringa et al, 2014; Jacini et al, 2018) or in terms of hyper-connectedness, as it occurs in epilepsy and amyotrophic lateral sclerosis (Sorrentino et al, 2018). In fact, while, on the one hand, disconnectedness hinders efficient communication, hyper-connectedness, on the other hand, impairs brain flexibility (Sorrentino et al, 2020).…”
Section: Introductionmentioning
confidence: 99%